Transformation of socio-political communication in the digital age and clarification of scientific definitions (Herald of Journalism, 2021)
The article examines the issues of transformation of social relations and their strengthening through the forms of communication in the new era, the problems of integration of socio-political communica- tion and the improvement of scientific definitions, the processes used.The purpose of the investigation. Analyzing the basic models of the theory of political communica- tion, the author tries to prove the hypothesis that instead of centralized one-way communication comes a form of information dissemination with enhanced feedback communication and inter-audit communi- cation. This is due to the fact that digital technologies lead to the increase of “horizontal” streams with “vertical” communication between participants in the exchange of information. The value of research. The author establishes interdependence between the reduction of political and social activity of the citizen and the absence of feedback from the political structure with society. Such dependence is valued as a factor that aggravates the dissatisfaction of society with the actions of the authorities. Metodologiya research includes in itself such scientific methods as observation and comparison, writing, systematiza- tion of facts and sociometric methods.Results of the scientific article. The article systematizes and analyzes the role and changes in the competencies of socio-political communication in the conditions of rapid development of the digital environment. Recommendations on the unification of scientific definitions used in the study of the pro- cesses of socio-political communication are developed. For example, on the basis of official documents are given the grounds for the use of the concept of “means of mass communications” and “means of mass information”.The article highlights the communicative approaches that enhance the influence and dynamics of social processes in political life and are factors that increase activity in society.Key words: communication interaction, vertical communication, political actors, socialization, me- diacracy.